NUCLEAR FUSION: COMPARISON OF NUCLEAR FUSION PERFORMANCE WITH INERTIAL AND MAGNETIC CONFINEMENT - Suryabh Prakash (International Educational Journal of Science and Engineering, 2025)
This research paper provides an initial summary of nuclear fusion and the physics behind the process of creating a successful fusion reaction. Ultimately, the paper compares the performance of nuclear fusion reactors that use inertial confinement techniques to those using magnetic confinement. The analysis of existing fusion reactor data was taken into account by analyzing the triple product for existing fusion reactors. Data has shown that the highest triple product to be achieved by NIF, which is an inertial confinement reactor, and the triple product indicated for inertial confinement are greater. The conclusive reason for the greater triple product for inertial confinement is the higher plasma density achieved despite the confinement time being in the order of nanoseconds.